Flexibility Factors of Unreinforced Branch Pipe Connections Subjected to In-Plane and Out-of-Plane Bending Moments for Fixed-Simply End Conditions - ลำธาร สดใส; พิมสาร มนต์ศักดิ์ (Engineering and Technology Horizons, 2020)
Flexibility factors are an important parameter in pipe stress analysis, especially, for branch pipe connections subjected to external moments, in-plane and out-of-plane. Inaccuracy of these can influence to calculated moments which result in inaccurate displacement stress range. The purpose of this paper is to investigate the effects of lengths of the run and branch pipeson flexibility factors and correlation equations for these flexibility factors on geometry parameters (d/D, D/T, t/T) for range 0.333 £ d/D £ 1, 20 £ D/T £ 250 and 0.333 £ t/T £ 3 subjected to in-plane and out-of-plane bending moments for fixed-simply end conditions. Finite element method with linear elastic property is employed for stress and flexibility factor evaluation. At first, FEM stress results of run-branch pipe intersection are verified by comparing with the available experimental data, the study on effect of lengths for the run and branch pipes, the determination of flexibility factors and correlation equations for these flexibility factors was carried out, respectively. The simulated result, the stress distribution trend, shows good agreement with the experimental data. Moreover, the FEA simulations of varying lengths of the run and branch pipes and fixed-simply end conditions, were performed and the calculated results indicate that run and branch pipe lengths have an effect on flexibility factors.